PELATIHAN PEMBUATAN DAFTAR PUSTAKA DENGAN MENDELEY BAGI MAHASISWA, SMA SEDERAJAT DAN UMUM - Iin Emy Prastiwi; Abdul Haris Romdhoni; Agus Subekti (LPPM ITB AAS Indonesia Surakarta, 2022)
This activity was carried out with the background of wanting to help parties who need it in using the Mendeley application. The purpose of this community service is to increase knowledge through direct practice on how to use the Mendeley application in making references to scientific papers or thesis. It is hoped that the results of this training will provide direct practice of using Mendeley to general students, high school / vocational students, the general public and parties in need. This activity is carried out using the lecture method, direct discussion, simulation practice using the Mendeley application. The lecture method is used in the process of delivering training/socialization materials. The expected output targets of this activity are 1) The public is able to know how to use Mendeley in making references to scientific papers and theses; 2) People find solutions to problems in using Mendeley.